Cluster-based industrial development : Kaizen management for MSE growth in developing countries - Sonobe, Tetsushi; Otsuka, Keijiro; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book attempts to provide an effective strategy for industrial development based on the KAIZEN management training experiments conducted in Ghana, Kenya, Ethiopia, Vietnam, and Tanzania. We focus on micro and small enterprises (MSEs) in industrial clusters, because clusters consisting of MSEs are ubiquitous and have high potential to grow.
Keywords: Management; Industries; Industrial organization; Development economics; Economic growth